Pengaruh Varietas dan Sistem Tanam pada Karakteristik Daun Rumput Gajah dalam Tumpang Sari dengan Gliricidia Sepium: The Effect of Varieties and Planting Systems on the Characteristics of Elephant Grass Leaves in Intercropping with Gliricidia sepium - Prasetyo, Prasetyo; Dhia Arkan, Naofal; Sugiharto, Indra; Hidayat, Nur; Harwanto, Harwanto; Rahmadian Ulfah, Annistia; Prihambodo, Tri Rachmanto; Cahyani, Wilis (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study investigated an intercropping system using two improved Napier grass varieties, consisting of cultivar Pakchong (Pennisetum purpureum cv. Thailand) and cultivar Red Napier (Pennisetum purpureum cv. Red) grown in combination with Gliricidia sepium. The research aimed to determine the effects of grass variety and planting system on leaf quality and chlorophyll content. An experimental design based on a Randomized Complete Block Design (RCBD) factorial was employed, consisting of 2 treatment varieties and 2 treatment planting systems in four replications, for a total of 16 experimental plots, each consisting of 3 m x 3 m and 1.5 m spacing, covering 279 m². The treatments combined two varieties (V1 = Red Napier; V2 = Pakchong) with two planting systems (S1 = monoculture; S2 = intercropping). Variables measured included leaf length, leaf width, leaf area, chlorophyll a, chlorophyll b, and total chlorophyll content. Analysis of variance (ANOVA) showed that variety had a highly significant effect (p<0.01) on leaf width and a significant effect (p<0.05) on leaf area. Mean comparison indicated that the V2S1 (Pakchong–monoculture) treatment produced the greatest leaf width, 3.07 ± 0.03 cm, and the largest leaf area 2837.82±118 cm², outperforming all other treatments. Chlorophyll content did not significantly change in all treatments. It is concluded that the Pakchong in a monoculture system improves leaf width and leaf area but does not improve leaf chlorophyll content.